LOW LEVEL NEUROLOGICAL STATES PADA SDH DAN EDH POST KRANIOTOM TINJAUAN TERMINOLOGI DIAGNOSIS TERAPI PROGNOSIS - Dini Fajri Hastuti*, Al Rasyid*, Mursyid Bustami*, Lyna Soertidewi* (Neurona Majalah Kedokteran Neuro Sains, 2010)
BRAIN INJURY IS THE MOST OFTEN CASE INTRACRANIAL BLEEDING SUCH AS EPIDURAL HEMATOMA EDH AND SUBDURAL HEMATOMA SDH IS TWO THINGS OF BRAIN HEMORRHAGES THAT WOULD BE HAPPEN IN TRAUMATIC BRAIN INJURY AND LOW LEVEL NEUROLOGICAL STATES LLNSS COULD BE AS AN OUTCOME IN TRAUMATIC BRAIN INJURY THERE REMAINS MUCH UNCERTAINTY IN DIAGNOSING LLNSS IN THIS ARTICLE WE REVIEW THE TERMINOLOGY DIAGNOSIS THERAPY AND PROGNOSIS LLNSS IN PATIEN WITH HISTORY OF TRAUMATIC BRAIN INJURY